Ulcerative colitis with Guillain–Barré syndrome: A case report. Issue 25 (June 2018) - Liu, Zhengru; Zhou, Ke; Tian, Shan; Dong, Weiguo
Abstract: Rationale: Ulcerative colitis is a chronic and recurrent inflammatory disease involving the intestine. It is reported that about 40% of patients with ulcerative colitis have extraintestinal manifestations, where as the literature on neurological involvement as extraintestinal manifestation is rather limited. Guillain-Barré syndrome is an abnormal immune-mediated and acute-acquired demyelinating disease that mainly affects the peripheral nervous system and often has a phenomenon of protein-cell separation of cerebrospinal fluid. Here, we report a rare case of ulcerative colitis with Guillain-Barré Syndrome. Patient concerns: We described a patient with Guillain-Barré syndrome during the remission period of ulcerative colitis. Clinical manifestations are the numbness of the upper extremities, weakness in the limbs and the inability of the fingers companion. Cerebrospinal fluid (CSF) showed albuminocytological dissociation and electromyography suggested neurogenic lesion. Diagnoses: Ulcerative colitis with Guillain-Barré syndrome was diagnosed based on the history of ulcerative colitis, related symptoms, typical cerebrospinal fluid albuminocytological dissociation and evidence of neurogenic injury through electromyography. Interventions: The patient was treated with intravenous (IV) methylprednisolone. Outcomes: After the treatment of glucocorticoid, the symptoms of the nervous system were disappeared. Lessons: Neurological involvement of extraintestinal manifestation during the remission period of ulcerative colitis also exists in the clinic. This case highlights the need for diagnostic vigilance in cases of ulcerative colitis involving the peripheral nerves during the remission period. We recommend cerebrospinal fluid examination and electromyography in view of rare but serious possibility of Guillain-Barré syndrome.